Murabahah in Contemporary Islamic Banking: An Analysis of the Maudhu’i Hadith in the Indonesian Context - Fadli Daud Abdullah; Hamdan Fathurrahman; Helmina; Doli Witro; Dindin Saepudin (Al-Muamalat, 2025)
This study aims to examine the practice of Murabahah contracts in Indonesian Islamic banking through a Maudhu’i approach to the hadith of the Prophet Muhammad, as a response to concerns about ethical deviations. Although Murabahah is commonly used as a financing instrument, this study assesses its normative and applicative suitability with the principles of hadith. The method employed is a qualitative descriptive-analytical analysis of 4 main hadiths and 42 supporting hadiths from Imam al-Bukhari, Nasa’i, and other Rawi. The results of the study indicate that the principles of Murabahah, such as price clarity, ownership of goods, and mutual agreement, have a strong foundation in authentic hadith, particularly Bukhari No. 1926 and Nasa’i No. 4571. Three main themes were identified: justice and willingness, the validity of deferred payment (nasi’ah), and the prohibition of gharar and hidden usury. In principle, Murabahah is permissible, but its implementation often violates the valid conditions of the contract. This study emphasises the importance of hadith literacy for industry practitioners and the role of the Sharia Supervisory Board (DPS). The implications are the need for standardisation of digital contracts and harmonisation of bank operations with hadith values to ensure the conformity of Murabahah with the objectives of Sharia law.